Kajian Toksikologi dan Penanggulangan Senjata Kimia - Raini, Mariana (Jurnal Kefarmasian Indonesia, 2009)
A chemical weapon is deﬁned as a substance that is intended for use in military and non- military operations to kill, seriously injure or otherwise incapacitate people, or to harm or destroy their habitat or economy. Chemical weapons can be made by toxic chemicals reaction. Chemical weapons misused may lead to terror, injury, death and environmental damage The Chemical Weapons Convention (CWC) is an arms control agreement which outlaws the production, stockpiling and use of chemical weapons. C WC is the Convention on the Prohibition of the Development, Production, Stoclqoiling and Use of Chemical Weapons and on their Destruction. This article describe how to idenlijji chemical weapons, sign and symptom of their toxicity, impact and the chemical weapons convention, in order to handle and control chemical weapons release.